Teff: Nutrient composition and health benefits - Baye, Kaleab (International Food Policy Research Institute, 2014)
Teff (Eragrostis tef), has been cultivated and used for human consumption in Ethiopia for centuries. However, teff’s global use for human consumption has been restrained partly due to limited knowledge about its nutrient composition and the processing challenges faced in making teff-based food products. Over the past decade, the recognition that teff is gluten-free has raised global interest. Consequently, literature on the nutritional composition, processing quality, and health benefits of teff has grown considerably. The existing literature suggests that teff is composed of complex carbohydrates with slowly digestible starch. Teff has a similar protein content to other more common cereals like wheat, but is relatively richer than other cereals in the essential amino acid lysine. Teff is also a good source of essential fatty acids, fiber, minerals (especially calcium and iron), and phytochemicals such as polyphenols and phytates.